2003
DOI: 10.1088/0967-3334/25/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Hydration status measurement by radio frequency absorptiometry in young athletes—a new method and preliminary results

Abstract: A new method for non-invasive measurement of the human state of hydration is presented. This method is based on frequency-dependent absorptiometry of radio-waves passing through tissues. A device utilizing this method was constructed and applied to 12 young (24 +/- 1) male volunteers, who were dehydrated for 1-2.5% of their weight by performance of a physical effort (two 30 min bouts of treadmill walking/running at 2, 3, 4, 5, 6 and 7 mph, 5 min at each speed, separated by 10 min rest), under moderate heat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In 2003, Moran et al [33] demonstrated the use of electromagnetic waves for assessment of hydration on 12 male subjects in a climatic chamber. The subjects were subjected to heat stress in various degrees.…”
Section: Radio Frequency Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2003, Moran et al [33] demonstrated the use of electromagnetic waves for assessment of hydration on 12 male subjects in a climatic chamber. The subjects were subjected to heat stress in various degrees.…”
Section: Radio Frequency Methodsmentioning
confidence: 99%
“…The results are affected by changes in posture, exercise, and sodium chloride balance in the body. Some researchers have argued that plasma osmolality is only valid for changes in hydration state but not for estimating TBW [33]. The volume and concentration fluctuate with daily activities and do not respond quickly to loss of body fluid after exercise or other daily activities.…”
Section: Analysis Of Blood Samplementioning
confidence: 99%
See 1 more Smart Citation
“…CSF production is around 500 ml per day and it is renewed about four times every 24 hours [13, 15]. As told, reduction of the CSF turnover rate has been described in aging and in AD [13-14].…”
Section: Technical Reportmentioning
confidence: 99%
“…In addition to these basic techniques, a number of elegant systems have been developed for use in the field to determine hydration [48]. These systems include portable refractometers to determine urine specific gravity, as well as portable urine conductivity analyzers [54] and arm radio frequency analyzers [55]. These portable instruments accurately predict urine osmolality and body mass loss, respectively [48].…”
Section: Measurement Of Cognitive Thirst Sensation In Humansmentioning
confidence: 99%